Adenomatoid Tumor of the Adrenal Gland: Report of Two Cases and Review of the Literature - Guan, Jiexia; Zhao, Chang; Li, Hengming; Zhang, Wenjing; Lin, Weizhen; Tang, Luying; Chen, Jianning (Frontiers in Endocrinology, 2021)
Adenomatoid tumor (AT) is an uncommon benign neoplasm of mesothelial origin, usually occurring in the female and male genital tracts. Extragenital localization such as the adrenal gland is extremely rare. Until now, only 39 cases of adrenal AT have been reported in the English literature. Here we report two novel cases of adrenal AT occurred in male patients aged 30 and 31 years. The tumors were discovered incidentally by computed tomography (CT). Macroscopically, the tumors were unilateral and solid and the greatest dimension of the tumors was 3.5cm and 8.0cm, respectively. Histologically, the tumors consisted of angiomatoid, cystic and solid patterns and infiltrated the adrenal cortical or medullary tissue. The tumor cells had low nuclear/cytoplasmic ratio, with no pathological mitosis or nuclear pleomorphism. Thread-like bridging strands and signet-ring-like cells could be seen. Immunohistochemically, the tumor cells were positive for epithelial markers (AE1/AE3, CK7) and mesothelial markers (D2-40, calretinin and WT-1). The Ki-67 index was approximately 1% and 2%, respectively. The differential diagnosis of adrenal AT includes a variety of benign and malignant tumors. The patients had neither local recurrence nor distant metastasis at 21 months and 8 months after removal of the tumor. In the literature review, we comprehensively summarized the clinical, morphological, immunohistochemical and prognostic features of adrenal AT. Adrenal ATs are morphologically and immunophenotypically identical to those occur in the genital tracts. Combining the histology with immunohistochemical profiles is very supportive in reaching the diagnosis of this benign tumor, helping to avoid misdiagnosis and overtreatment.